Peginterferon lambda for the treatment of HBeAg-positive chronic hepatitis B: A randomized phase 2b study (LIRA-B) - Chan, Henry L.Y.; Ahn, Sang Hoon; Chang, Ting-Tsung; Peng, Cheng-Yuan; Wong, David; Coffin, Carla S.; Lim, Seng Gee; Chen, Pei-Jer; Janssen, Harry L.A.; Marcellin, Patrick; Serfaty, Lawrence; Zeuzem, Stefan; et al. (Journal of hepatology, 2016)
Peginterferon lambda-1a (lambda) is a Type-III interferon, which, like alfa interferons, has antiviral activity in vitro against hepatitis B virus (HBV) and hepatitis C virus (HCV); however, lambda has a more limited extra-hepatic receptor distribution. This phase 2b study (LIRA-B) evaluated lambda in patients with chronic HBV infection. Adult HBeAg+ interferon-naive patients were randomized (1:1) to weekly lambda (180μg) or peginterferon alfa-2a (alfa) for 48weeks. The primary efficacy endpoint was HBeAg seroconversion at week 24 post-treatment; lambda non-inferiority was demonstrated if the 80% confidence interval (80% CI) lower bound was >−15%. Baseline characteristics were balanced across groups (lambda N=80; alfa N=83). Early on-treatment declines in HBV-DNA and qHBsAg through week 24 were greater with lambda. HBeAg seroconversion rates were comparable for lambda and alfa at week 48 (17.5% vs. 16.9%, respectively); however lambda non-inferiority was not met at week 24 post-treatment (13.8% vs. 30.1%, respectively; lambda vs. alfa 80% CI lower bound −24%). Results for other key secondary endpoints (virologic, serologic, biochemical) and post hoc combined endpoints (HBV-DNA <2000IU/ml plus HBeAg seroconversion or ALT normalization) mostly favored alfa. Overall adverse events (AE), serious AE, and AE-discontinuation rates were comparable between arms but AE-spectra differed (more cytopenias, flu-like, and musculoskeletal symptoms observed with alfa, more ALT flares and bilirubin elevations seen with lambda). Most on-treatment flares occurred early (weeks 4–12), associated with HBV-DNA decline; all post-treatment flares were preceded by HBV-DNA rise. On-treatment, lambda showed greater early effects on HBV-DNA and qHBsAg, and comparable serologic/virologic responses at end-of-treatment. However, post-treatment, alfa-associated HBeAg seroconversion rates were higher, and key secondary results mostly favored alfa. ClinicalTrials.gov number: NCT01204762.